Brazil’s Catalyst Effect on Middle Powers Foreign Policy - Núnez Gómez, Katy Giselle; Němec, Jan, 1980 srpen 23.-; Doležal, Tomáš; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2018)
This research is a contribution to the field of Foreign Policy Convergence focusing on Latin America and the Caribbean. The objective of the research is to find the connection between power asymmetries vis-à-vis Brazil and the degree of convergence of Chile and Mexico’s foreign policy. To conduct to this research the study uses the method of Comparative Case Study Analysis using Brazil, Mexico and Chile as case studies. The research analysis 13 Government Program documents from 2000 to 2018 and it also analysis 140 documents posted on each of the countries Ministries of Foreign Affairs. Looking to similarities, differences, patterns and causality, the study found that Mexico and Chile’s foreign policy had converged as a reaction to perceived power asymmetries vis-à-vis Brazil during its rise as a regional power. However, the degree of intensity of foreign policy convergence has been related to the political ideology of the governments in power; increasing when centre-right presidents have held office and decreasing when centre-left presidents have been in power. It had also varied according to Brazil’s perception of strength; when Brazil has been perceived as economic and politically strong the degree of foreign policy convergence has increased, while it has decreased when Brazil had been perceived as economically and politically weak. Finally, the degree of convergence has also been linked to current international issues; the arrival of Donald Trump and its protectionist measures which had impacted mainly Brazil and Mexico had not only increase the degree of convergence between Mexico and Chile, but among the three countries.
Vedoucí práce: Jan Němec
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses